Harvard Business Review on winning negotiations. (Boston : Harvard Business Review Press, 2011)
It will help you to seal or sweeten a bargain by uncovering the other side's motives, conquer faulty assumptions to make the right deals, forge deals only when they support your strategy, set the stage for a healthy relationship long after the ink has dried, make promises you can keep, gain your adversaries trust in high-stakes talks and know when to walk away.
Investigative negotiation / Deepak Malhotra and Max H. Bazerman -- Deals without delusion / Dan Lovallo, Patrick Viguerie, Robert Uhlaner and John Horn -- Breakthrough bargaining / Deborah M. Kolb and Judith Williams -- Building deals on bedrock / David Harding and Sam Rovit -- Getting past yes: negotiating as if implementation mattered / Danny Ertel -- Negotiating without a net: a conversation with the NYPD's Dominick J. Misino / Diane L. Coutu -- Six habits of merely effective negotiators / James K. Sebenius -- The fine art of friendly acquisition / Robert J. Aiello and Michael D. Watkins -- Negotiating the spirit of the deal / Ron S. Fortgang, David A. Lax, and James K. Sebenius -- When to walk away from a deal / Geoffrey Cullinan, Jean-Marc Le Roux, and Rolf-Magnus Weddigen.
Contains articles previously published in the Harvard Business Review.
Includes bibliographical references and index.
Keywords: Negotiation; Negotiation in business